2007
DOI: 10.1080/00933104.2007.10473336
|View full text |Cite
|
Sign up to set email alerts
|

Dividing the Digital Divide: Instructional Use of Computers in Social Studies

Abstract: This article explores the impact of social class setting on the instructional decisions made by four high school social studies teachers in utilizing computers in their classrooms. First, teachers in different settings had dissimilar views of the educational futures of their students. Second, the students with the highest and lowest social class status used computers more for school assignments than other students. Third, teachers in the two higher social class settings provided instruction that gave their stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
8
0
1
Order By: Relevance
“…El cambio metodológico necesario para afrontar la integración de las herramientas digitales en la enseñanza de las Ciencias Sociales se convierte, por tanto, y junto a la potenciación de la competencia digital docente, en aspectos fundamentales a trabajar desde la formación del profesorado (Miguel-Revilla, Martínez-Ferreira y Sánchez-Agustí, 2020). Después de todo, la investigación destaca que los profesores tienden a reforzar sus métodos de trabajo tradicionales una vez que introducen el factor tecnológico en sus clases, evitando transformar o complementar su enfoque pedagógico (DeWitt, 2007 Dicho en otras palabras, la mera introducción de las tecnologías es incapaz de modificar el modelo de enseñanza, y debido al riesgo de acabar utilizando herramientas digitales para reforzar prácticas tradicionales, se apunta como conveniente la reflexión docente sobre sus metas y su propia práctica (Swan y Hicks, 2006). Como apuntan Gómez Carrasco, Miralles, López Facal y Prats, "el uso de estos medios debe servir para fomentar el pensamiento autónomo, creativo y crítico", evitando caer en la mera reiteración de la metodología tradicional a través de nuevos recursos (Gómez Carrasco et al, 2017, p. 225).…”
Section: Evolución De Las Esperanzas Y Reticencias Ante El Uso De La unclassified
“…El cambio metodológico necesario para afrontar la integración de las herramientas digitales en la enseñanza de las Ciencias Sociales se convierte, por tanto, y junto a la potenciación de la competencia digital docente, en aspectos fundamentales a trabajar desde la formación del profesorado (Miguel-Revilla, Martínez-Ferreira y Sánchez-Agustí, 2020). Después de todo, la investigación destaca que los profesores tienden a reforzar sus métodos de trabajo tradicionales una vez que introducen el factor tecnológico en sus clases, evitando transformar o complementar su enfoque pedagógico (DeWitt, 2007 Dicho en otras palabras, la mera introducción de las tecnologías es incapaz de modificar el modelo de enseñanza, y debido al riesgo de acabar utilizando herramientas digitales para reforzar prácticas tradicionales, se apunta como conveniente la reflexión docente sobre sus metas y su propia práctica (Swan y Hicks, 2006). Como apuntan Gómez Carrasco, Miralles, López Facal y Prats, "el uso de estos medios debe servir para fomentar el pensamiento autónomo, creativo y crítico", evitando caer en la mera reiteración de la metodología tradicional a través de nuevos recursos (Gómez Carrasco et al, 2017, p. 225).…”
Section: Evolución De Las Esperanzas Y Reticencias Ante El Uso De La unclassified
“…In particular, social studies and history education are still sometimes characterized by the use of technology as a mere supplement for traditional teaching practices, without any change in pedagogical models (DeWitt, 2007;Swan and Hicks, 2006). Not all educators have embraced the new possibilities offered by technology, and while a gap can still be detected between early adopters and laggards even today (Bolick, 2017), social studies teachers are not only expected to introduce technology in educational contexts, but also to use it to promote effective student learning and to foster civic practices (Hicks et al, 2014).…”
Section: Educational Technology and New Opportunities For History Educationmentioning
confidence: 99%
“…However, students in the affluent schools engaged in more high-quality research and analysis with technology than students in the non-affluent schools. DeWitt (2007) found that higher SES students receive greater computer access and use than low SES students. Teachers at schools with predominantly high SES students provide their students with more time to use computers in class, in technology centers and at home to complete a variety of computer-based assignments.…”
Section: Technology Use In Social Sciencementioning
confidence: 96%
“…Other research illustrates the challenges associated with providing students class time to complete projects and presentations on computers. DeWitt (2007) found that social science teachers in schools that served mostly low SES students felt overburdened presenting the state-mandated content standards. This pressure to cover the material limited low SES students' opportunities to construct projects and presentations on computers.…”
Section: Student Uses O F Technology In Social Sciencementioning
confidence: 99%
See 1 more Smart Citation